Investigation of genetic diversity using molecular and biochemical markers associated with powdery mildew resistance in different flax (Linum usitatissimum L.) genotypes - Marwa M. Ghonaim; Marian M. Habeb; Mahmoud T. M. Mansour; Heba I. Mohamed; Ahmed A. A. Omran (BMC Plant Biology, 2024)
Abstract Under greenhouse conditions, the resistance of 18 different genotypes of flax to powdery mildew was evaluated. To investigate genetic diversity and identify the molecular and biochemical markers linked to powdery mildew resistance in the tested genotypes, two molecular marker systems—start codon targeted (SCoT) and inter-simple sequence repeat (ISSR)—as well as a biochemical marker (protein profiles, antioxidant enzyme activity, and secondary metabolites) were used. Based on the results, the genotypes were classified into four categories: highly susceptible, susceptible, moderately susceptible, and moderately resistant. The genotypes differed significantly in powdery mildew severity: Polk had a severity of 92.03% and Leona had a severity of 18.10%. Compared to the other genotypes, the moderately resistant genotypes had higher levels of flavonoids, antioxidant enzymes, phenolics, and straw yield; nevertheless, their hydrogen peroxide and malondialdehyde levels were lower. Protein profiles revealed 93.75% polymorphism, although the ISSR marker displayed more polymorphism (78.4%) than the SCoT marker (59.7%). Specific molecular and biochemical markers associated with powdery mildew resistance were identified. The 18 genotypes of flax were divided into two major clusters by the dendrogram based on the combined data of molecular markers. The first main cluster included Leona (genotype number 7), considered moderate resistance to powdery mildew and a separate phenetic line. The second main cluster included the other 17 genotypes, which are grouped together in a sub-cluster. This means that, besides SCoT, ISSR markers can be a useful supplementary technique for molecular flax characterization and for identifying genetic associations between flax genotypes under powdery mildew infection.